Miniature Circuit Breaker (MCB) Current Detector by using Microcontroller and Global System of Mobile (GSM) - Md Husin, Noor Farhana; Mohd Jamail, Nor Akmal (Evolution in Electrical and Electronic Engineering, 2022)
Rising electricity consumption has important implications for economic growth and trade. Although the increased electrical energy consumption is necessary to develop income, pollution, uncertainties, and environmental issues have the potential to become major national challenges. The main problem that had been solved is that electrical hazards in residential areas are frequently linked with malfunctioning home appliances and surging appliance demand, which occurred in overloading. The prevailing electrical distribution system is insufficiently protected and does not provide sufficient warning to the household. The focus of the project is on how to overcome the conventional operation of a Miniature Circuit Breaker (MCB) and improve the system by continuously monitoring electricity usage to optimise system management and minimise hazards caused by electrical faults. MCB Current Detector has been developed by using a microcontroller which is Arduino MEGA and GSM SIM900A Module. This system detects a current reading in the protective region of the MCB, directly logged to MicroSD Card and sent an alert signal to the household in the form of a light indicator, an alarm, and an SMS message. As a result, the homeowner can take precautions as needed and assist the wireman with maintenance. In the meantime, this system can assist in the reduction of electricity bills. The prototype has been created and been tested on four (4) types of a load of home electrical appliances, the load was a 5W smartphone charger, 2200W electrical kettle, 45W table fan, and 750W bread toaster. The results of the test show the prototype had sent a notification to the user based on the current reading flow.